The Level of Application of Strategic Management Accounting Initiatives And Its Impact on Financial and Non-Financial Performance: A Field Study on Industrial Companies Listed in The Saudi Financial Market - Alamri, Ahmad (The Arab Journal of Administration, 2023)
This study aimed to identify the level of application of Strategic Management Accounting Initiatives (SMAIs) represented by the activity-based costing (ABC) system, the Just-in-Time (JIT) system, Total Quality Management (TQM), and the Balanced Scorecard (BSc) in industrial companies listed in the Saudi financial market, and its impact on their financial and non-financial performance. The descriptive analytical method was used to achieve the objectives of the study, and the questionnaire was used as a tool for data collection. The researcher distributed the study questionnaire to a sample of (300) accountants or financial managers in (30) industrial companies, and retrieved (240) of them valid for analysis. The results of the study showed that the level of application of the SMAIs under study by the surveyed companies was moderate, and there was a positive impact of company’s age and size and the competition intensity it faces on the level of application of these initiatives. The results of the regression analysis also showed a positive impact of the level of application of the SMAIs under study on the level of financial and non-financial performance of the companies under study.